Structural, compositional, mechanical characterization and biological assessment of bovine-derived hydroxyapatite coatings reinforced with MgF2 or MgO for implants functionalization - OKTAR, FAİK NÜZHET (ELSEVIER SCIENCE BV, 2016)
Hydroxyapatite (HA) is a consecrated biomaterial for bone reconstruction. In the form of thin films deposited by pulsed laser technologies, it can be used to cover metallic implants aiming to increase biocompatibility and osseointegration rate. HA of animal origin (bovine, BHA) reinforced with MgF2 (2 wt.%) or MgO (5 wt.%) were used for deposition of thin coatings with improved adherence, biocompatibility and antimicrobial activity. For pulsed laser deposition experiments, a KrF* (lambda = 248 nm, T-EWHM <= 25 ns) excimer laser source was used. The deposited structures were characterized from a physical-chemical point of view by X-Ray Diffraction, Fourier Transform Infra-Red Spectroscopy, Scanning Electron Microscopy in top- and cross-view modes, Energy Dispersive X-Ray Spectroscopy and Pull-out adherence tests. The microbiological assay using the HEp-2 cell line revealed that all target materials and deposited thin films are non-cytotoxic. We conducted tests on three strains isolated from patients with dental implants failure, i.e. Microccocus sp., Enterobacter sp. and Candida albi cans sp. The most significant anti-biofilm effect against Microcococcus sp. strain, at 72 h, was obtained in the presence of BHA:MgO thin films. For Enterobacter sp. strain a superior antimicrobial activity at 72 h was noticed, in respect with simple BHA or Ti control. The enhanced antimicrobial performances, correlated with good cytocompatibility and mechanical properties recommend these biomaterials as an alternative to synthetic HA for the fabrication of reliable implant coatings for dentistry and other applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Bovine bone; Reinforced hydroxyapatite; Highly adherent coatings; Titanium; Pulsed laser deposition; PULSED-LASER DEPOSITION; THIN-FILMS; IN-VITRO; NANO-HYDROXYAPATITE; SOL-GEL; SURFACE; INTERFACE; TI-6AL-4V; TI; OSTEOBLAST